The Effectiveness of Health Promoting Services on Self-care Behaviors and Health Status of Buddhist Monks In Photharam District, Ratchaburi Province - Laochot, Chomyong (Journal of Health Science of Thailand, 2017)
The purpose of this research was to study the effectiveness of health promotion services on self-care behaviors and health status of Buddhist monks who stayed in monastery during the rainy season in Photharam District, Ratchaburi Province. The study was a quasi-experimental research with one experimental group. The sample group received health promotion services during the years 2005-2011. Data collection was done before the experiment and afterwards by using interview and health evaluation form. Data analysis was performed by computing frequency, percentage, arithmetic mean, and Z-test. were used for statistical tests. The research results showed that Buddhist monks smoking were significantly decreased, Buddhist monks smoking ceassation were significantly increased (p 0.005 and p<0.000). On body mass index scale, obesity levels were not significantly decreased (p 0.158), waist circumference were significantly decreased (p 0.008). Their hospital admissions were significantly decreased (p<0.000). On fasting blood sugar scale, exceedances of the normal levels did not significantly increase, the risky levels significantly decreased (p 0.019). The research results showed that health promotion services were effectiveness on self-care behaviors and health status of Buddhist monks. Therefore, health promotion services could be beneficial with guideline on health-care enhancing activities developed for other Buddhist monks.